2020
DOI: 10.3390/antiox9080713
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Activity of Natural and Synthetic Antioxidants

Abstract: Numerous chronic diseases including cancer, cardiovascular, chronic respiratory or neurodegenerative diseases, diabetes mellitus, retinal damage, and others are associated with oxidative stress [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Nowadays, the data provided by in vitro and in vivo tests and the association between exogenous antioxidants and their metabolites in the generated therapeutic effects have made antioxidants a hot topic for research [ 226 ]. Despite the phenolic structure that allowed the elucidation of polyphenols’ redox mechanisms, the direct correlation of the antioxidant effect with the beneficial effects in KOA through their metabolites is extremely deficient.…”
Section: The Effects Of Antioxidants In Koamentioning
confidence: 99%
“…Nowadays, the data provided by in vitro and in vivo tests and the association between exogenous antioxidants and their metabolites in the generated therapeutic effects have made antioxidants a hot topic for research [ 226 ]. Despite the phenolic structure that allowed the elucidation of polyphenols’ redox mechanisms, the direct correlation of the antioxidant effect with the beneficial effects in KOA through their metabolites is extremely deficient.…”
Section: The Effects Of Antioxidants In Koamentioning
confidence: 99%
“…These two cytoprotective systems are related in complex functional crosstalk, i.e., (a) some direct antioxidants are required for the catalytic functions of redox proteins and (b) several antioxidant proteins participate in the synthesis and/or homeostasis of direct antioxidants. Direct antioxidants are diverse and common in nature but, importantly and less explored, many inducers of cytoprotective proteins have been isolated from edible plants, e.g., sulforaphane from broccoli and curcumin from turmeric [108,109]; ergothioneine, polyphenols and flavonoids from a variety of edible mushrooms [110,111] and DHA (but not arachidonic acid, the most abundant n-6 LCPUFA, or eicosapentaenoic acid, EPA, the second important n-3 LCPUFA) from different sources, mainly marine fish and invertebrates [112,113].…”
Section: Dha: the Ultimate Indirect Antioxidantmentioning
confidence: 99%
“…Some antioxidants directly scavenge ROS. On the other hand, some induce the Keap1–Nrf2 pathway, resulting in an increased anti-oxidative capacity [ 35 , 36 , 37 ]. Here, we demonstrated that 3-HT and CDA directly scavenged ROS: they counteracted DPPH radicals.…”
Section: Discussionmentioning
confidence: 99%